Phase transformation in the system TlBi(Te1-xSex)(2) - Chrissaris, K.; Vinga, E. S.; Özer, Mehmet; Paraskevopoullos, K. M.; Polychroniadis, E. K. (Wiley-V C H Verlag GMBH, Po Box 10 11 61, D-69451 Weinheim, Germany, 2004)
TlBiTe2 and TlBiSe2 -that are ternary analogs of the IV-VI semiconductors-, although they crystallize in the same space group R (3) over barm (D-3d(5)), exhibit different behaviour during heating. The observed phase transformation depends on Se content (x) in the system TIBi(Te1-xSex)(2) and the transformation disappears by increasing Se content after a certain value (x=0.25). This dependence is examined through the analysis of the DSC non-isothermal measurements and an attempt for the explanation of the observed behaviour is undertaken through the consideration of off - center atoms. (C) 2004 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim
Keywords: phase transformation; off-center; DSC; narrow gap; chalcogenides; plasma; Ictac Kinetics Project; Computational Aspects; Tlbite2; Growth